The impact of supraventricular ectopic complexes in different age groups and risk of recurrent atrial fibrillation after antiarrhythmic medication or catheter ablation. (1st January 2018) - Alhede, Christina; Lauridsen, Trine K.; Johannessen, Arne; Dixen, Ulrik; Jensen, Jan S.; Raatikainen, Pekka; Hindricks, Gerhard; Walfridsson, Haakan; Kongstad, Ole; Pehrson, Steen; Englund, Anders; Hartikainen, Juha; et al.
Abstract: Introduction: Supraventricular ectopic complexes (SVEC) are known risk factors of recurrent atrial fibrillation (AF). However, the impact of SVEC in different age groups is unknown. We aimed to investigate the risk of AF recurrence with higher SVEC burden in patients ± 57 years, respectively, after treatment with antiarrhythmic medication (AAD) or catheter ablation (CA). Methods: In total, 260 patients with LVEF > 40% and age ≤ 70 years were randomized to AAD (N = 132) or CA (N = 128) as first-line treatment for paroxysmal AF. All patients underwent 7-day Holter monitoring at baseline, and after 3, 6, 12, 18 and 24 months and were categorized according to median age ± 57 years. We used multivariate Cox regression analyses and we defined high SVEC burden at 3 months of follow-up as the upper 75th percentile > 195 SVEC/day. AF recurrence was defined as AF ≥ 1 min, AF-related cardioversion or hospitalization. Results: Age > 57 years were significantly associated with higher AF recurrence rate after CA (58% vs 36%, p = 0.02). After CA, we observed a higher SVEC burden during follow-up in patients > 57 years which was not observed in the younger age group treated with CA (p = 0.006). High SVEC burden at 3 months after CA was associated with AF recurrence in older patients but not in younger patients (> 57 years: HR 3.4 [1.4–7.9], p = 0.005). We did not find any age-related differences after AAD. Conclusion: We found that younger and older patients respond differently to CA and that SVEC burden was only associated with AF recurrence in older patients.